A novelsolar-driven power/desalination system based on a liquid metal magnetohydrodynamic unit. (1st February 2022) - Abdollah Nezhad, Qasem; Jafarmadar, Samad; Khalilarya, Shahram
Highlights: A new combined power and desalination cycle driven by solar energy is proposed. Liquid metal MHD was used for power generation instead of conventional rotary turbines. Total power of 38.3 kW and fresh water of 881.6 L/h were produced. By cogeneration, the energy and exergy efficiencies can be improved by 150.2% and 4.3%, respectively. Abstract: In comparison with the conventional turbine-based power unit, liquid metal magnetohydrodynamic (LMMHD) power units have simple structure since they have no moving parts, and hence they are highly reliable systems with low maintenance cost. However, a LMMHD power unit needs a high-temperature prime mover which is conventionally provided by fossil fuels. To cover up this shortcoming, the present study aims at proposing a new LMMHD cogeneration plant for power and fresh water supply, using a concentrated solar power (CSP) system. The devised integrated system was designed and evaluated from the first- and second-laws of thermodynamics perspectives. The results indicated that the proposed cogeneration plant can produce total power of 38.3 kW and fresh water of 881.6 L/h, in which in this case the energy utilization factor (EUF) and total exergy efficiency were computed 99.69% and 5.57%, respectively. Considering the LMMHD power unit as the reference system, it is found that when the idea of cogeneration was employed, the energy and exergy efficiencies of the LMMHD power system can be improved by 150.2% and 4.3%, respectively. Among all constituents, the receiver has the highest exergy destruction of 256.9 kW, followed by the heliostat with exergy destruction of 228.2 kW. The results of parametric study indicated that the energy and exergy efficiencies of the proposed cogeneration system can be improved by increasing the humidifier/dehumidifier effectiveness or decreasing the mass flow rate of the second MHD loop.